Omega-3 fatty acids in critical illness. (7th October 2014) - Martin, Julie M; Stapleton, Renee D
Abstract : Supplementation of enteral nutritional formulas and parenteral nutrition lipid emulsions with omega-3 fatty acids is a recent area of research in patients with critical illness. It is hypothesized that omega-3 fatty acids may help reduce inflammation in critically ill patients, particularly those with sepsis and acute lung injury. The objective of this article is to review the data on supplementing omega-3 fatty acids during critical illness; enteral and parenteral supplemental nutrition are reviewed separately. The results of the research available to date are contradictory for both enteral and parenteral omega-3 fatty acid administration. Supplementation with omega-3 fatty acids may influence the acute inflammatory response in critically ill patients, but more research is needed before definitive recommendations about the routine use of omega-3 fatty acids in caring for critically ill patients can be made.